Analisis Analisis Implementasi Pendekatan Etnosains dalam Pembelajaran IPA - Danang Habib Pratama; Jumadi Jumadi (Postgraduate, University of Mataram, 2023)
Content analysis research aims to provide a literature review in the use of ethnoscince approaches in science learning. This analytical research uses a descriptive analysis method with a qualitative approach. Article documents were obtained through the Google Schoolar and Sinta pages using the keywords